PERLINDUNGAN HUKUM TERHADAP KREDITOR KECIL MELALUI PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) SEBAGAI SARANA RESTRUKTURISASI UTANG DEBITOR (Studi Kasus Pada PT Mandala Airlines) - , Jamaslin Purba ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research on Legal Protection of Small Creditor through Suspension of Payment based on Act Number 37 of 2004 Regarding Bankruptcy and Suspension of Payment (UUPKPU) As a Tool to Restructure Debtorâs Debt (Case Study of PT Mandala Airlines) is a normative legal research. Data used are secondary data obtained from literature research and are analyzed by mean of qualitative analysis. Objectives of the present research are i.e. (1) to analyze the legal protection, provided by Institution of Suspension of Payment as stipulated in UUKPKPU, of creditor with small amount of claim, and (2) to analyze the legal protection obtained by parties (debtor or creditor) in relation to the approval of suspension of payment petition requested by PT Mandala Airlines through Decision of Commercial Court at District Court of Jakarta Pusat Number: 01/PKPU/2011/Pn.Niaga.Jkt.Pst